INNOVATIVE INSIGHTS INTO SOCIO-DEMOGRAPHIC FACTORS, CURRENT PRACTICES, AND OPPORTUNITIES FOR SUSTAINABLE SWEET POTATO FARMING IN BATAAN - Abuan, Abigail; Flordeliz, Edessa; Valdez, Walter G (Agricultural Socio-Economics Journal, 2026)
This study analyzes the socio-demographic characteristics and agricultural practices of 66 sweet potato farmers in a rural community, examining cultivation methods, farmer profiles, and production challenges. The research reveals that most farmers are middle-aged males with high school education or less, operating small to medium-sized farms using primarily rainfed irrigation systems. Ube emerges as the predominant sweet potato variety cultivated in the region. Farmers demonstrate heavy reliance on commercial fertilizers and chemical pesticides for crop management, though some express interest in organic alternatives. Significant challenges include pest infestations, particularly Ulalo, and inadequate post-harvest storage facilities. Marketing approaches are evenly split between direct sales and middleman transactions, indicating diverse distribution strategies. A critical finding highlights the absence of formal agricultural training among farmers, despite widespread willingness to participate in educational programs. This gap represents a substantial opportunity for intervention. The study identifies pest management, storage infrastructure, and farmer education as priority areas requiring attention. Current practices suggest potential for improving sustainability through integrated pest management and enhanced storage techniques.These findings provide essential baseline data for developing targeted agricultural extension programs and policy initiatives. The research supports evidence-based interventions to enhance sweet potato production efficiency, sustainability, and farmer livelihoods in the community, while addressing the identified training deficit that could significantly impact agricultural outcomes.